Operational issues and lessons learned during National Iron Plus Initiative documentation in Eastern India - Vikas Bhatia; Swayam P Parida; Preetam B Mahajan; Sasmita Pradhan (Wolters Kluwer Medknow Publications, 2019)
Anaemia is a condition in which red blood cells have fewer haemoglobin molecules than normal, or fewer red blood cells overall, and thus less ability to carry oxygen to tissues in the body. Nutritional anaemia is a major public health problem in India and is primarily due to iron deficiency. Symptoms of iron deficiency anaemia are primarily non specific and become apparent when there is severe anaemia. The National Iron Plus Initiative (NIPI) is the most ambitious and comprehensive anaemia control programme in the world. The process documentation team conducted 170 interviews in March, April and May 2016 among officials and frontline workers at state, district, block, sector/cluster and field levels and among NIPI beneficiaries in Odisha. To achieve variation in responses and to get full set of information on how NIPI was being implemented, process documentation and survey data were collected in four districts of Odisha- Keonjhar, Jagatsinghpur, Bhadrak and Kalahandi. This review will give an overview about the operational issues encountered during the National Iron Plus Initiative documentation in Odisha.